Usability Evaluation of the Mobile Banking Application By Hijra Bank Using the User Experience Questionnaire Method - Setiawan, Agus - (Jurnal Akuntansi dan Keuangan Syariah (Jurnal Akunsyah), 2024)
The rapid growth of mobile banking technology requires special attention to user experience so that applications can be used efficiently and satisfactorily. App users perform a series of tasks designed to cover the app's key features, while researchers observe and record responses, difficulty, and time required to complete the tasks. The results of usability testing provide in-depth insight into the specific problems users face when using the Hijra Bank mobile banking application. Next, the User Experience Questionnaire (UEQ) is used to measure qualitative aspects of user experience, such as satisfaction, fear, stimulation, and concentration. Data from UEQ is used to identify design elements that contribute positively or negatively to the user experience. The results of this research provide an in-depth view of the strengths and weaknesses of the mobile banking application by Hijra Bank in Indonesia. This information can be used by application developers to make necessary improvements and improvements, ensuring that users have a satisfactory and efficient experience when using mobile banking services by Hijra Bank. This research also contributes to increasing awareness and understanding in the development of user-oriented mobile banking applications by Hijra Bank in Indonesia.